Polymorphic microsatellite markers in the brown seaweed Fucus vesiculosus - Candeias, Rui (2015)
Background: Fucus vesiculosus is a brown seaweed dominant on temperate rocky shores of the northern hemisphere and, is typically distributed in the mid-upper intertidal zone. It is an external fertilizer that reproduces sexually, providing an excellent model to address conflicting theories related to mating systems and sexual selection. Microsatellite markers have been reported for several Fucus species, however the genomic libraries from where these markers have been isolated, have originated from two or more species pooled together (F. vesiculosus and F. serratus in one library; F. vesiculosus, F. serratus and Ascophyllum nodosum in a second library), or when the genomic DNA originated from only one species it was from Fucus spiralis. Although these markers cross-amplify F. vesiculosus individuals, the level of polymorphism has been low for relatedness studies. Findings: The microsatellite markers described here were obtained from an enriched genomic library, followed by 454 pyrosequencing. A total of 9 microsatellite markers were tested across 44 individuals from the North of Portugal. The mean number of alleles across loci was 8.7 and the gene diversity 0.67. Conclusions: The high variability displayed by these microsatellite loci should be useful for paternity analysis, assessing variance of reproductive success and in estimations of genetic variation within and between populations.